Analisis Pengadaan Jasa Influencer pada Satuan Kerja Pemerintah: Studi Kritis - Jamila Lestyowati; Mandar Trisno Hadisaputra (Direktorat Sistem Perbendaharaan, 2021)
Abstract Researches on the procurement of goods and services were carried out in any aspects, such as management, economics, law, finance and others. Many researches on procurement were conducted on various types of goods and services. However, it was a few researches discussed influencer procurement. Influencers are individuals with ability and skills to influence other parties due to their existing competencies. Many private companies hire influencers to promote their products or services. If it is seen from government side, there are many influencers used to disseminate policies. Influencers hiring requires procurement of goods and services. This study aims to evaluate influencer procurement in government work units. The research method was juridical empirical using primary and secondary data. Primary data came from interviews which were conducted with informants regarding the theme of influencer procurement to obtain field conditions. Secondary data came from legal materials in the form of statutory regulations and literature searches, and they were research results, news, and other secondary sources. The results showed that influencers were hired because of their wider reach with a large number of followers. The procurement of influencers was included in the category of procurement of goods which was specific to goods / other services / consulting services which were exempted, they were in the procurement of goods and services whose implementation was in established business practices. Abstrak Penelitian mengenai pengadaan barang dan jasa dilakukan pada banyak aspek, misalnya manajemen, ekonomi, hukum, keuangan dan sebagainya. Penelitian tentang pengadaan juga banyak dilakukan pada beragam jenis barang dan jasa. Namun sangat sedikit yang membahas pengadaan influencer. Influencer merupakan individu dengan kemampuan dan keterampilan untuk memengaruhi pihak lain disebabkan kompetensi yang ada padanya. Selama ini influencer banyak dimanfaatkan oleh perusahaan swasta untuk memasarkan produk atau jasanya. Dari sisi pemerintah sendiri, mulai banyak penggunaan influencer untuk menyebarluaskan kebijakan. Penggunaan influencer memerlukan kegiatan pengadaan barang dan jasa. Penelitian bertujuan untuk mengevaluasi pengadaan influencer pada satuan kerja pemerintah. Metode penelitian adalah yuridis empiris menggunakan data primer dan sekunder. Data primer berasal dari wawancara yang dilakukan kepada informan terkait tema pengadaan influencer untuk mendapatkan kondisi lapangan. Data sekunder berasal dari bahan hukum berupa peraturan perundang-undangan dan penelusuran kepustakaan yaitu hasil penelitian, berita maupun sumber sekunder lainnya. Hasil penelitian menunjukkan bahwa influencer digunakan karena jangkauannya yang lebih luas dengan jumlah pengikut yang banyak. Pengadaan influencer masuk pada kategori pengadaan barang bersifat khusus terhadap barang/jasa lainnya/ jasa konsultansi yang dikecualikan yaitu pada pengadaan barang dan jasa yang pelaksanaannya berada pada praktik bisnis yang mapan.